Leadership Beyond Reason how great leaders succeed by harnessing the power of their values, feelings, and intuition - Townsend, John. (Oasis Audio, 2009)
Who we are on the inside can determine leadership success more than what we do or what we know. In Leadership Beyond Reason, Dr. Townsend explores the critical role of the leader?s internal world, the world of passion, emotions, intuition, creativity, values, self-awareness, conscience, and spiritual life. Unveiling links between personal and organizational success or failure and the contents of a leader?s ?heart,? the author shows that leaders excel not just through skill and smarts but by connecting with others using competencies, like curiosity, attention, reality assessment, distortion detecting, relationship building, ownership, and living with ambiguity. This is the leadership book only a world-respected psychologist could have written, and it is revolutionary in its insight.
Keywords: Leadership